On the occurrence of Apostolepis phillipsi (Serpentes, Elapomorphini) in Brazil, with the description of a new specimen from Mato Grosso - Colli, Guarino Rinaldi; Barreto-Lima, André Felipe; Dantas, Pedro Tourinho; Morais, Carlos José S.; Pantoja, Davi Lima; de Sena, Arthur; de Sousa, Heitor Campos (Zootaxa, 2019)
We describe a specimen of Apostolepis phillipsi Harvey, 1999, from Vila Bela da Santíssima Trindade, Mato Grosso, establishing the first unambiguous record of the species in Brazil. The new locality is ca. 120 km from the type locality, in Bolivia. We present an updated species diagnosis, the first image of a living specimen, and the first description of A. phillipsi coloration in life. Even though the Brazilian range of A. phillipsi lies within a protected area (Parque Estadual Serra Ricardo Franco—PESRF), it is threatened by cattle raising, logging and agriculture. PESRF lacks formal delimitation and a management plan, and the Mato Grosso State Legislature is considering a decree to extinguish PESRF, which could cause the extirpation of the Brazilian range of several endemic species.